Dakwah Majelis Dzikir Islahul Ummah di Gerung Lombok Barat - Udin, MS; Saladin, Bustami (Jurnal Komunikasi Islam, 2021)
Da'wah means encouraging people to do good and preventing them from doing evils according to Allah's instructions. In a broad sense, da'wah is not only intended to convey the message of Islam to non-Muslims in order to convert to Islam, but it also to lead someone who has bad morals (naughty people) to return to the right path of Allah Swt. This article examines the role of the Majelis Dzikir of Islahul Ummah in West Lombok in conducting da'wah. Using descriptive qualitative research methods and in-depth interviews, this study concludes that this majelis dhikr is able to preach effectively to Gerung community. It can be seen form the provided data that number of followers of this majelis dhikr has continued to increase around 700 worshipers. In terms of the quality, the majority of the congregation admitted that have experienced the quality of positive changes: from bad to good; from good to better.